EFFECTIVENESS OF THE MOTOR RELEARNING APPROACH IN PROMOTING PHYSICAL FUNCTION OF THE UPPER LIMB AFTER A STROKE - Suneel Kumar Immadi; Kiran Kumar Achyutha; Dr. Amaranth Reddy; Krishna Priya Tatakuntla (International Journal of Physiotherapy, 2015)
Background:More than decades Stroke is one of the most frequently occurring disabling disease in the world. Reduced upper extremity function affects the ability to perform activities of daily living, which is likely to reduce independence, function of upper extremity is more difficult than the lower extremity. It can seriously impact the progress of rehabilitation. Methods: 60 outpatients are identified irrespective of hemorrhagic or thrombotic stroke, among those 30 patients received 40 1-h sessions in eight weeks (5 days/week) of conventional physiotherapy programme taken as group-A and another 30 patients were received 40 1-h sessions in eight weeks (5 days/week) of Motor relearning programme taken as group-B. Results: After the treatment sessions Patients who received motor relearning programme showed significantly better functional ability when assessing their functional status by task oriented performance than the conventional physiotherapy programme in both outcome scoring values, mean age of the subject who participated in study is 51 years. FMA (n=30 post-test mean=32.27 GROUP-A post-test mean=43.80 GROUP-B T test value t = 5.3743, p- value= < 0.0001) WMFT (n=30 post-test mean=39.80 GROUP-A, post-test mean=71.45 GROUP-B T test value t = 10.3401, p- value= < 0.0001) Conclusion: Motor relearning programme is found to be effective than the conventional physical therapy programme for enhancing functional recovery of the upper limb in stroke patients.